Anterior cruciate ligament tissue stiffness and anterior tibial translation are increased in patients with medial meniscus posterior root tear - Yavuz Selim Karatekin; Harun Altınayak; Ahmet Serhat Genç; Mirsad Yalçınkaya; Mehmet Seyfi Buruk; Orhan Balta (Journal of Orthopaedic Surgery and Research)
Abstract Introduction To evaluate the structural and functional relationship between medial meniscus posterior root tear (MMPRT) and anterior cruciate ligament (ACL), the aim was to assess the structure and elasticity of the ACL in patients with MMPRT and to measure tibial anterior translation. Materials and Methods Between January and June 2024, 56 patients (study group) were diagnosed with unilateral MMPRT on magnetic resonance imaging (MRI) and 31 healthy volunteers (control group) were included in the study. While the tibial anterior translation of the patients was evaluated using the KT 1000 device, the structure and stiffness of the ACL were assessed with ultrasound shear wave elastography (SWE). The tibial slope measurement was taken at 30 degrees of knee flexion on true lateral radiographs where the femoral condyles overlapped. Results A total of 87 participants were included in the study, consisting of 31 volunteers (25 females, 6 males) and 56 patients diagnosed with MMPRT (48 females, 8 males). The average SWE values of the ACL were compared between the study group (26.6 ± 8.9 kPa) and the control group (21.2 ± 5.7 kPa), with the study group demonstrating a significantly higher value (p: 0.004). In patients with MMPRT, the measurements of anterior translation using the KT 1000 device were an average of 6.19 ± 1.4 mm in the affected knees and 4.9 ± 0.78 mm in the unaffected knees. The comparison revealed a significantly greater anterior translation in the knees with MMPRT (p < 0.05). Multivariable regression analysis demonstrated a significant positive relationship between ACL SWE values and tibial slope (β = 1.11; CI, 0.24–1.99; P: 0.01). Conclusions Greater tibial anterior translation was observed on the side with MMPRT in the patients. There is a correlation between MMPRT and the stiffness of the ACL, which exhibits a higher elastic modulus. Additionally, an increase in tibial slope significantly affects the stiffness of the ACL. Level of evidence Level III, retrospective cohort study.